HERBAL EXTRACTS AND THEIR ANTIFUNGAL ACTIVITY AGAINST MALASSEZIA FURFUR - SARIKA, K.M.; APARAJITA V.; BINDU RANI; SOOSAMMA, M. (International Journal of Pharma and Bio Sciences, 2013)
Malassezia furfur, is a dermatophilic fungi that utilizes the secretions of the sebaceous glands for its growth and causes infections like dandruff and associated secondary infections. Herbal based treatments for dandruff are now gaining more significance over the conventional synthetic anti-dandruff remedies. In our study, efficacy of 23 medicinal plants for their antifungal activity was evaluated .Aqueous and ethanolic herbal extracts were used for the assay. The Minimum Inhibitory Concentration or MIC was determined as per guidelines laid down by Clinical and Laboratory Standards Institute and the antifungal activity was assayed by well diffusion method.In our study Malassezia furfur was found to be most susceptible to the aqueous extracts of Eugenia jambolana and least susceptible to Terminalia paniculata and among the ethanolic extracts it was most susceptible to Quisqualis indica and least susceptible to Terminalia paniculata.